PEMANFAATAN GOOGLE SITES SEBAGAI MEDIA PEMBELAJARAN BERBASIS WEB - Vederico Pitsalitz Sabandar; Widya Putri Ramadhani (German für Gesellschaft (J-Gefüge), 2023)
The community service activities carried out aim to train educators so they can utilize and apply the use of the Google sites in creating web-based learning media. The training, which was carried out through community service activities, was centered on teachers at SMP Negeri 85 Central Maluku, Hatu Village, Central Maluku Regency, Maluku. The training is a form of effort to support the government in education units in improving the quality of human resources in the era of Society 5.0. Activities were carried out using lecture, demonstration, and question and answer methods with the number of participants involved as many as 14 people who were then used as respondents. The instrument used is a questionnaire that aims to determine the level of an understanding or initial and final knowledge of the teacher regarding the training material provided. The results of the activities carried out show that before the training, it was found that on average 53% of the training participants did not understand, 34% had understood, and 13% were known to have understood the Google sites and its use. On the other hand, after the training, the average lack of understanding decreased by 51% to 2% and as many as 85% of the training participants became familiar with the Google sites and its use as a web-based learning medium. These results indicate that the training carried out has increased understanding and has had a good and positive impact on the trainees